ต้นทุนฐานกิจกรรมและการวัดประสิทธิภาพการใช้รถบรรทุกสำหรับการขนส่งแบบเต็มคัน - นราธิป ธนบดีธาดา (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To explore the business process and the cost structure for truck load operation. The thesis also develops a spreadsheet-based application for analyzing activity-based-costing and truck efficiency measurement. The study identifies the structuring of costs associated with truck-load operation that enables a more accurate estimation of costs than the traditional accounting practices. The truck load carriers would then have a better understanding of the relationship between the activities performed and the resulting costs and would be able to use the cost estimates for service pricing or business process improvement.